The participation of university students: a case study: Participación cívica, social y universitaria entre los estudiantes de la Universidad Complutense de Madrid (UCM) - Hernández Fernández, Coral; Alcoceba Hernando, José Antonio; Homont, Louis Pierre Philippe (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Citizen participation is included by the United Nations as a privileged way to meet the Sustainable Development Goals of the 2030 Agenda. A quantitative study was conducted among the UCM students to analyse their citizen and university participation. The main results show that, although there is a good predisposition towards social and university involvement, participation in specific actions is a minority. The lack of information and ignorance of the options, together with the scarcely proactive attitude of young people seem to be the reasons for this lack of participation.